Pemanfaatan Limbah Tebon Jagung sebagai Silase Pakan Ternak Terfermentasi - Sarijan, Abdullah; Doloksaribu, Budi; Djaja, Irba; DAS, Kurniawan; Farahningtyas, Diva Aulia (Universitas Pahlawan Tuanku Tambusai, 2026)
The Village Partner Development (VPD) program, themed “Utilization of Corn Stem Waste as Fermented Silage for Animal Feed,” is a form of community service implemented by lecturers at Musamus University in Merauke in various villages/ sub-districts in Merauke Regency. This program aims to improve community understanding, knowledge, and skills in utilizing agricultural waste, specifically corn stems, as fermented animal feed during the dry season. The program was conducted in Kuper Village, Semangga District, Merauke Regency, from August to October 2025, in collaboration with partner farmers and livestock groups. The VPD program included lectures, training, feed preparation practices, monitoring and evaluation of the sustainability of the activities by farmers and livestock. Through this community service activity, livestock farmers can produce fermented feed by utilizing corn stems, which is currently largely wasted. Livestock farmers who initially did not understand the fermentation technology for producing animal feed became able to comprehend and manufacture animal feed independently.